La dinamica familiar factor importante en niños , jovenes y adolescentes del Centro Diurno de desarrollo integral para personas con discapacidad Mies Loja y la intervenciòn del trabador social. - Muima Guevara, Patricia del Carmen (2015)
A problem that affects the entire family. The impact produced, as well as vary in families and the individuals that form it, changes according to the stage where you are in each one. Having a disabled child/a, can be devastating for parents in particular and also for the other children. The families undergo big changes and tensions that influence their family dynamics which specifically affects the development and well-being of persons with disabilities. The present research work starts from the detected problem by "The little attention of the adolescent and young family of children attending to the" day centre of Integral Development for people with disabilities of the Ministry of economic and Social-Loja Inclusion "" , was raised as a goal: strengthen family care to achieve the integral development of children, adolescents and young people who attend the "Center day of Integral Development for people with disabilities of the Ministry of economic and Social-Loja Inclusion. -Based categories and variables of the object of study, to obtain a better understanding of the problem to be investigated, to determine the causes and effects that generate little attention afforded the family to persons with disabilities, and designing a participatory Action Plan aimed at the families of persons with disabilities to strengthen the attention and care that improves the quality of life. The this research and intervention in reality model was based on the methodology of the abstract to the concrete by means of its four phases: the first being the sensitive phase, the phase of technical information, the participating research phase, and determination phase, taking into account the review of each of the documents in relation to the object of study. The study focused on 25 parents and 10 teachers, data that can then be studied, systematized and analyzed determined the issues already addressed. The main findings were that parents not give the necessary attention to the care 5 of their children because of the time they devote to their work and lack of knowledge of how give adequate attention to their children with disabilities, which in turn affects negatively the integral development of people with disabilities